Analisis Akuntabilitas dan Transparansi Pengelolaan Dana Pnpm Mandiri Pada Badan Keswadayaan Masyarakat Betul Kota Malang - Vivi Dwi Aryanti; Masiyah Kholmi; Endang Dwi Wahyuni (Journal of Accounting and Investment, 2013)
The aims of this study is to describe the accountability and transparency of PNPM Mandiri fund management in self supporting public agency (BKM) BETUL Malang by using indicators of accountability and transparency that have been determined by Indonesian governement. Object of the research is BKM BETUL. The data obtained from the questionnaires spread result and documentation relate the rule of BKM BETUL funding management in 2010-2011. The analysis showed that the accountability and transparency PNPM Mandiri fund management in BKM BETUL, from 13 indicators of accountability to ideal conditions, there were 10 indicators of accountability are fulfilled so the percentage obtained is 77%, which means that the condition is included in the fourth interval that is accountable. From 6 indicators transparency into ideal conditions, there are five indicators of transparency are fulfilled, so the percentage obtained is 83%, which means that the condition is included in the fourth interval that is transparent. Based on the analysis, it can be concluded that the PNPM Mandiri management of funds in the BKM BETUL been accountable and transparent.